Peace operations and global order - Bellamy, Alex J., 1975-; Williams, Paul D., 1975- (London : Routledge, 2010)
This book investigates the changing role of peacekeeping and competing perspectives about what the role should be, demonstrating the close links between peacekeeping, conflict prevention and conflict resolution.
Originally published: 2005.
Transferred to digital printing 2008.
Includes bibliographical references and index.
Keywords: Peacekeeping forces; Conflict management; War -- Prevention; Conflict management; Peacekeeping forces; War -- Prevention